(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this paper, the research focus is on the longitudinal stability of a wheeled mobile robot, using a geometric similarity coefficient (this coefficient is defined in the paper). The research method used for calculations is D'Alembert's principle. The results represent the limit driving/braking forces and limit accelerations/ decelerations for a given geometric similarity coefficient, before the robot loses stability.